Effects of Different Levels of Intra-Abdominal Pressure on the Postoperative Hepatic Function of Patients Undergoing Laparoscopic Cholecystectomy: A Systematic Review and Meta-Analysis. Issue 5 (October 2018) - Cheng, Zheng-Jun; Wang, Yun-Bing; Chen, Long; Gong, Jian-Ping; Zhang, Wei
Abstract : Objective: The aim of this meta-analysis is to compare the differences in postoperative markers of the hepatic function under different intra-abdominal pressures in laparoscopic cholecystectomy (LC). Methods: Several databases were searched for control studies, and then the weighted data were pooled with random-effect models. Results: A total of 11 studies involving 865 patients were included. The meta-analysis reveals that the level of the aspartate aminotransferase and alanine transaminase of the low-pressure group has a lower postoperative increase than the moderate-pressure group ( P <0.001). The level of the aspartate aminotransferase and alanine transaminase of the moderate-pressure group has a lower postoperative increase than the high-pressure group ( P <0.001). Totally, the effect of lower pressure LC on postoperative hepatic functions is less significant than that of the higher one. Potential subgroup analysis does not modify these results. Conclusions: The recommended pressure in LC is suggested to be lower so as to result in a better surgical safety, especially for special populations. Abstract : Supplemental Digital Content is available in the text.